A simulation study on memory characteristics of InGaZnO-channel ferroelectric FETs with 2D planar and 3D structures. (1st May 2022) - Mo, Fei; Mei, Xiaoran; Saraya, Takuya; Hiramoto, Toshiro; Kobayashi, Masaharu
Abstract: We have investigated the memory characteristics of InGaZnO (IGZO)-channel ferroelectric FETs (FeFETs) with 2D planar and 3D structures by TCAD simulation to improve the memory window (MW) with a floating-body channel for high-density memory applications. From the study on 2D planar FeFETs with a single gate and a double gate, the MW depends on channel length ( L ) and is enhanced with shorter L due to stronger electrostatic coupling from the source and drain to the center region of the IGZO layer. From the study on 3D structure FeFETs with macaroni (MAC) and nanowire (NW) structures, a large MW can be obtained especially in NW FeFETs due to the electric field concentration by Gauss's law in the 3D electrostatics. Furthermore, we have systematically studied and discussed the device design of MAC and NW structure FeFETs in terms of the diameter and thickness for high-density memory applications. As the IGZO thickness and the outer diameter of the IGZO layer decrease, the MW increases due to the voltage divider and the electric field concentration. The device parameters that can maximize the MW can be determined under the constraints of the layout and material based on this study.